Strategi Penerapan Media Pembelajaran Sesuai Perspektif Kurikulum Merdeka di MAN Binjai Sumatera Utara - Neliwati; Abdullah Fikri Sholehuddin; Carles Harahap; Rizza Fikri Al-Faris (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to explore: First, evaluate the level of understanding and ability of MAN Binjai teachers in implementing learning media that supports the principles of the Independent Curriculum. Second, knowing the strategies that can be implemented to optimize the use of learning media in accordance with the Independent Curriculum at MAN Binjai. Third, knowing the obstacles faced in implementing learning media at MAN Binjai, knowing the strategies that can be implemented to optimize the use of learning media in accordance with the Independent Curriculum at MAN Binjai. This research method is a qualitative type with a descriptive approach. The instruments used in this research were observation, interviews and documentation studies. The location of this research is MAN Binjai, North Sumatra. This research data analysis uses three steps, data reduction, data presentation and conclusion drawing. The research results show that: First, the implementation of the independent curriculum at MAN Binjai includes the implementation of intracurricular learning, extracurricular learning, and the Pancasila Rahmatan Lil Al-Amin (P5RA) Student Profile Strengthening Project. This independent curriculum emphasizes freedom to think, innovate, learn independently and creatively, as well as the freedom to feel happy. Second, the planning strategy for using interactive digital learning media at MAN Binjai begins with intensive training for teachers to integrate technology in their teaching process. The use of digital media also helps students develop technological skills which are very important in the modern era. The research results show that the use of interactive digital learning media at MAN Binjai has increased student engagement, expanded access to learning, and developed their digital skills. Third, the obstacles faced by Technological Infrastructure: One of the main obstacles is the availability of adequate technological infrastructure. Training Limitations: Despite intensive training, there are still challenges in obtaining adequate training for all teachers. Teacher Readiness and Willingness: Not all teachers have the same readiness in adopting and integrating digital learning media. Insufficient Content: Sometimes, the availability of appropriate and quality content to support project-based learning can be a challenge. Time Limitations: Implementing interactive digital learning media requires additional time for preparation and development of learning content. Student Engagement: While digital learning media can increase student engagement, there are also challenges in ensuring that all students can access and use the technology effectively.